High-grade Follicular Lymphomas Exhibit Clinicopathologic, Cytogenetic, and Molecular Diversity Extending Beyond Grades 3A and 3B. (2nd October 2021) - Laurent, Camille; Adélaïde, José; Guille, Arnaud; Tesson, Bruno; Gat, Elodie; Evrard, Solene; Escudié, Frederic; Syrykh, Charlotte; Canioni, Danielle; Fabiani, Bettina; Meignin, Véronique; Chassagne-Clement, Catherine; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Although follicular lymphoma (FL) is usually graded as FL1-2, FL3A, and FL3B, some borderline cases can be observed and led us to investigate the clinicopathologic diversity of grade 3 FL (FL3). Among 2449 FL patients enrolled in Lymphoma Study Association (LYSA) trials, 1921 cases with sufficient material underwent a central pathologic review. The resulting diagnoses comprised 89.6% FL1-2 (n=1723), 7.2% FL3A (n=138), and 0.5% purely follicular FL3B (n=9). The remaining 51 unclassifiable cases (2.7%) exhibited high-grade features but did not meet WHO criteria for either FL3A or FL3B; and were considered as "unconventional" high-grade FL (FL3U). FL3U morphological pattern consisted of nodular proliferation of large cleaved cells or small-sized to medium-sized blast cells. Compared with FL3A, FL3U exhibited higher MUM1 and Ki67 expression, less BCL2 breaks and more BCL6 rearrangements, together with a higher number of cases without any BCL2, BCL6 or MYC rearrangement. FL3U harbored less frequent mutations in BCL2, KMT2D, KMT2B, and CREBBP than FL3A. MYC and BCL2 were less frequently mutated in FL3U than FL3B. Rituximab cyclophosphamide, doxorubicin, vincristine, and prednisone treated FL3U patients had a worse survival than FL1-2 patients with similar follicular lymphoma international prognostic index and treatment. These results suggest that high-grade FLs encompass a heterogeneous spectrum of tumors with variable morphology and genomic alterations, including FL3U cases that do not strictly fit WHO criteria for either FL3A or FL3B, and display a worse outcome than FL1-2. The distinction of FL3U may be useful to allow a better comprehension of high-grade FLs and to design clinical trials.